Structural basis of PP2A inhibition by small t antigen. - Uhn Soo Cho; Seamus Morrone; Anna A Sablina; Jason D Arroyo; William C Hahn; Wenqing Xu (PLoS Biology, 2007)
The SV40 small t antigen (ST) is a potent oncoprotein that perturbs the function of protein phosphatase 2A (PP2A). ST directly interacts with the PP2A scaffolding A subunit and alters PP2A activity by displacing regulatory B subunits from the A subunit. We have determined the crystal structure of full-length ST in complex with PP2A A subunit at 3.1 A resolution. ST consists of an N-terminal J domain and a C-terminal unique domain that contains two zinc-binding motifs. Both the J domain and second zinc-binding motif interact with the intra-HEAT-repeat loops of HEAT repeats 3-7 of the A subunit, which overlaps with the binding site of the PP2A B56 subunit. Intriguingly, the first zinc-binding motif is in a position that may allow it to directly interact with and inhibit the phosphatase activity of the PP2A catalytic C subunit. These observations provide a structural basis for understanding the oncogenic functions of ST.